Simple preparation of cuprous oxide nanoparticles for catalysis of azide–alkyne cycloaddition. (1st March 2018) - Amini, Mojtaba; Ramezani, Sakine; Anbari, Alireza Pourvahabi; Beheshti, Abolghasem; Gautam, Sanjeev; Chae, Keun Hwa
Cuprous oxide (Cu2O) nanoparticles were prepared by two simple methods and their structural, morphological and electronic properties were investigated by X-ray diffraction analysis, X-ray absorption near-edge structure, energy dispersive X-ray analysis and scanning electron microscopy. Cuprous oxide nanoparticles efficiently catalyse 1, 3-dipolar cycloaddition of a variety terminal alkynes and organic azides producing the corresponding 1, 2, 3-triazole derivatives in excellent yields without use of any additives. Phenylacetylene and benzyl chloride were chosen as model starting compounds for the optimisation of the reaction conditions, such as effect of solvent, reaction temperature and time of reaction in the presence of a-Cu2O nanoparticles as a catalyst. The results showed that using cuprous oxide nanoparticles (0.035 mmol) and heating at 70 °C in water, the reaction of phenylacetylene with benzyl chloride and sodium azide gave 1-benzyl-4-phenyl-1H-1, 2, 3-triazole almost quantitatively in 6 h of reaction time. A study of the recyclability and reusability of the catalyst revealed that a-Cu2O could be reused at least five times without significant loss of yield.